Pengaruh modal psikologis dan persepsi gayakepemimpinan transformasional terhadap workplace well being - Anita Yuniarti; Desi Yustari Muchtar (‎‎‎TAZKIYA Journal of Psychology, 2016)
This study aims to determine the effect of psychological capital and the perceptionof transformational leadership style to the workplace well being of employees.This study uses quantitative approach with multiple regression analysis involvinga sample of 220 civil servants of the Ministry X. The sampling technique usedin this study is a non-probability sampling. To measure workplace wellbeing,researchers compiled independently of workplace wellbeing scale based on thetheory of workplace well being developed by Page (2005). Then, the instrumentused to measure the psychological capital is Psychological Capital Quessionare24 (PCQ-24) developed by Luthans, Youssef & Avolio (2007). Furthermore,measuring instruments used to measure the perception of transformationalleadership is a modification of the measuring instrument multifactor Leadershipquestionnare factor (MLQ). Based on the results of hypothesis testing, firstconclusions obtained from this study is a significant difference of perceptionpsychological capital dan transformational leadership style on workplace wellbeing on the employees of the Ministry X. Then based on the results of tests ofsignificance of each regression coefficient on the dependent variable, there arefour variables were obtained significant regression coefficient values, namely; (1)hope dimension of psychological capital; (2) the dimension idealized influence oftransformational leadership style; (3) the dimensions of intellectual stimulationtransformational leadership style; and (4) individualized consideration dimensionsof transformational leadership style.